Neurodegenerative diseases reflect the reciprocal roles played by retroelements in regulating memory and immunity - Herbert, Alan (Frontiers in Neuroscience, 2024)
Tetrapod endogenous retroelements (ERE) encode proteins that have been exapted to perform many roles in development and also in innate immunity, including GAG (group specific antigen) proteins from the ERE long terminal repeat (LTR) family, some of which can assemble into viral-like capsids (VLCs) and transmit mRNA across synapses. The best characterized member of this family is ARC (activity-regulated cytoskeletal gene), that is involved in memory formation. Other types of EREs, such as LINES and SINES (long and short interspersed elements), have instead been exapted for immune defenses against infectious agents. These immune EREs identify host transcripts by forming the unusual left-handed Z-DNA and Z-RNA conformations to enable self/nonself discrimination. Elevated levels of immune EREs in the brain are associated with neurodegenerative disease. Here I address the question of how pathways based on immune EREs are relate to the memory EREs that mediate neural plasticity. I propose that during infection and in other inflammatory states, ERE encoded GAG capsids deliver interferon-induced immune EREs that rapidly inhibit translation of viral RNAs in the dendritic splines by activation of protein kinase R (PKR). The response limits transmission of viruses and autonomously replicating elements, while protecting bystander cells from stress-induced cell death. Further, the PKR-dependent phosphorylation of proteins, like tau, disrupts the endocytic pathways exploited by viruses to spread to other cells. The responses come at a cost. They impair memory formation and can contribute to pathology by increasing the deposition of amyloid beta.